Politisasi Konstitusi Piutang Negara di Indonesia - Agus Pandoman Pandoman (UIN Sunan Kalijaga Yogyakarta, 2014)
One example of the problems in the state's claim is BLBI extended by BankIndonesia to the national banking system, which has become the state's claim, but notresolved through PUPN, but further right to claim the government handed over toIBRA established by Presidential Decree No. 27 of 1998 . Since handed over to thegovernment the right to collect BI, BI ended authority to withdraw BLBI of thereceiving bank, resolved through non-litigation and mechanisms and the solution wasnot to use repressive laws. Receivables BLBI state is a case of default the unusuallylarge number (extraordinary default), but penyelesaianya by IBRA implemented withthe exclusion of the legal principles of the settlement of accounts receivable against thedebtor country BLBI receiver, so in this case the journey is also a cost for settlingdisputes outstanding a big. This paper would like to see how the practice of politicizingthe constitution that happens particularly with respect to issues of State receivables.